2023
DOI: 10.1001/jamasurg.2023.0662
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Intraoperative Hyperthermic Intraperitoneal Chemotherapy for Locally Advanced Colon Cancer

Abstract: ImportancePeritoneal metastasis in patients with locally advanced colon cancer (T4 stage) is estimated to recur at a rate of approximately 25% at 3 years from surgical resection and is associated with poor prognosis. There is controversy regarding the clinical benefit of prophylactic hyperthermic intraperitoneal chemotherapy (HIPEC) in these patients.ObjectiveTo assess the efficacy and safety of intraoperative HIPEC in patients with locally advanced colon cancer.Design, Setting, and ParticipantsThis open-label… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…More positive results were seen in the Spanish multicentre clinical trial HIPECT4, where HIPEC was given as an intraoperative treatment at the time of initial surgical resection 113 . A total of 184 patients with locally advanced primary colon (cT4N0–2M0) were randomized to radical tumour resection plus HIPEC with mitomycin C (30 mg/m 2 ; 60 min) compared to cytoreduction alone.…”
Section: Colon Cancermentioning
confidence: 99%
“…More positive results were seen in the Spanish multicentre clinical trial HIPECT4, where HIPEC was given as an intraoperative treatment at the time of initial surgical resection 113 . A total of 184 patients with locally advanced primary colon (cT4N0–2M0) were randomized to radical tumour resection plus HIPEC with mitomycin C (30 mg/m 2 ; 60 min) compared to cytoreduction alone.…”
Section: Colon Cancermentioning
confidence: 99%
“…In Reply I thank all the letter writers for their interest in our work. The multicenter phase 3 HIPECT4 was a randomized clinical trial that showed benefit in locoregional control rate with hyperthermic intraperitoneal chemotherapy (HIPEC) using mitomycin C in locally advanced colon cancer. The design of this study was focused on the surrogate primary end point of locoregional control rate at 3 years.…”
mentioning
confidence: 99%
“…To the Editor We read with great interest the study by Arjona-Sánchez and colleagues regarding the use of intraoperative hyperthermic intraperitoneal chemotherapy (HIPEC) for locally advanced colon cancer. In their study, the authors assessed the safety of mitomycin C (MMC)–based chemotherapy and its effect on local recurrence and disease-free survival.…”
mentioning
confidence: 99%